If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 + -2x = -1x + -3 Reorder the terms: 11 + -2x = -3 + -1x Solving 11 + -2x = -3 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 11 + -2x + x = -3 + -1x + x Combine like terms: -2x + x = -1x 11 + -1x = -3 + -1x + x Combine like terms: -1x + x = 0 11 + -1x = -3 + 0 11 + -1x = -3 Add '-11' to each side of the equation. 11 + -11 + -1x = -3 + -11 Combine like terms: 11 + -11 = 0 0 + -1x = -3 + -11 -1x = -3 + -11 Combine like terms: -3 + -11 = -14 -1x = -14 Divide each side by '-1'. x = 14 Simplifying x = 14
| -23=6r+12 | | 18r+4= | | -23=16r-5 | | 3x^2+2x-x=0 | | 5x+3=37x | | 54=8g+10-4(3g+12) | | 2(2x+40)=180 | | 54=8g+12-4(3g+12) | | 1x+5=10x | | 12-2y=y-6+3y | | 5(9x+13)=7(4x+10) | | -35+7+12-18-1-16= | | 2(6x+14)=7(8x+12) | | 2(x+8)=5(x+11) | | 16=3x-X | | X=27+-1Y | | 6=3y+9 | | 2(x+6)=5(x+12) | | 20-/2=50 | | 1.5x=24 | | 1.5=24 | | 15=300 | | 3p^2-5p+2=y | | ln(X-7)-5=2 | | X+Y+10=37 | | 2/9t=36 | | 3B+4B=24 | | 16-3+-4+2-12+2= | | x^4-tx^2+16=0 | | 121^3/2 | | 10-2f=15-3f | | 5m+4m=27m |